Microheterogeneous polymeric barriers for membrane contactors : study of gas and vapour separations. - Bessarabov, Dmitri Georgievich (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 1996.